ANALYSIS OF DIDACTICAL CONTRACTS ON TEACHING MATHEMATICS: A DESIGN EXPERIMENT ON A LESSON OF NEGATIVE INTEGERS OPERATIONS - Nyiayu Fahriza Fuadiah; Didi Suryadi; Turmudi Turmudi (Jurnal Infinity, 2017)
This paper presents an analysis of mathematical teaching that takes place in the classroom to identifying the characteristics of didactical contract that occur as part of a didactical situation. Didactical contract is a way that determines the responsibilities of teachers and students and regulates their interaction in a learning process. Arithmetic operations involving negative numbers are known to have epistemological obstacles that cause student difficulties in solving problems and understand the higher level subject matter. The design experiment was conducted on 31 seventh grade students and a mathematics teacher on negative integer operations lessons. The researchers analyzed the ongoing learning, how the didactic situational stages evolve in the teacher-student interaction that allows the formation of new knowledge or concepts in the student and how the teacher organizes the responsibility for achieving the learning objectives. The Analysis showed that students, at an early stage, can perform negative integers operations by utilizing the basic concepts they get in primary school. This concept can bridge into a new knowledge that identifies the properties of integer count operations and builds power of mind on problem-solving.